Enhancing the knowledge and economic of community through establishment of waste bank in Kundasang, Sabah - Abd Manaf, Latifah; Yaacob, Nurul Nadia Fatiha; Ho Nyuk Onn @ Ariffin, Mariani; Abdullah, Sabrina J. Ho; Mohamat Yusuff, Ferdius @ Ferdaus; Alias, Fatma Sabariah; Suhaimin, Japiril (Knowledge Transfer Programme, 2017)
Aware with eco-tourism interest, Kundasang community has set up Kelab Kebersihan dan Keindahan Kundasang (KBI) in order to preserve the cleanliness and beauty of Kundasang. Prior to the establishment of KBI, the local community volunteered to do cleaning activities around the town and the main roads in Kundasang. However, the lack of storage barrels, illegally sanitary disposal of wastes, improper solid waste management and the attitude of the community is a major obstacle that can affect the image of Kundasang in the eyes of tourists whose numbers are growing every single day. Thus, the aim of this project is to improve the waste management and increase the awareness towards recycling practice of community in Kundasang, Sabah. This project is at the first stage of transformation, which is more focused on the development and establishment of an operational for Waste Bank in Kundasang, Sabah. Graduate intern and the academia are responsible in developing a training module for members in KBI. It focuses on increasing the awareness towards cleanliness through training. This project aims to increase the knowledge of Kundasang community towards waste separation and improve the solid waste management in this area. It brings a positive feedback from the community as well as providing an economic benefit especially for individual, homestay entrepreneur, children and hawkers.